Further study on the second status connectivity index of graphs - Mahdieh Azari; Jia-Bao Liu (AKCE International Journal of Graphs and Combinatorics)
The second status connectivity index (SSC index, for short) of a simple connected graph [Formula: see text] is defined as the sum of the terms [Formula: see text] over all edges ab of [Formula: see text], where [Formula: see text], the status of a vertex a in [Formula: see text], is the sum of the distances between a and all other vertices of [Formula: see text]. The aim of the paper is to study the SSC index through investigating its behavior under various families of composite graphs and a number of mathematico-chemically interesting graphs derived from them.